2015
DOI: 10.1017/jfm.2015.578
|View full text |Cite
|
Sign up to set email alerts
|

Third-order resonant wave interactions under the influence of background current fields

Abstract: A series of experiments were conducted in a wave basin (50 m long, 10 m wide and 5 m deep) generating two waves propagating at an angle by a directional wavemaker. When the two waves were selected from a resonant triplet, an initially non-existing wave grew as the waves propagated down the tank. The linear growth rate of the resonating wave agreed well with third-order resonance theory based on Zakharov's reduced gravity equation. Additional experiments with opposing and coflowing mean current with large tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…Rapizo et al (2016) found that the development of the spectral tail is disturbed for waves propagating on a coflowing current, due to detuning of the quartet resonance interactions. Similarly, Waseda et al (2015) found that the spectral tail can be suppressed by detuning due to currents. Ice sheets also tend to suppress high-wavenumber components, attenuating the amplitude of high-wavenumber components more severely than low-wavenumber components (see Toffoli et al 2015;Meylan et al 2018), possibly suppressing the tail of the spectrum.…”
Section: Effect Of the High-wavenumber Tailmentioning
confidence: 84%
“…Rapizo et al (2016) found that the development of the spectral tail is disturbed for waves propagating on a coflowing current, due to detuning of the quartet resonance interactions. Similarly, Waseda et al (2015) found that the spectral tail can be suppressed by detuning due to currents. Ice sheets also tend to suppress high-wavenumber components, attenuating the amplitude of high-wavenumber components more severely than low-wavenumber components (see Toffoli et al 2015;Meylan et al 2018), possibly suppressing the tail of the spectrum.…”
Section: Effect Of the High-wavenumber Tailmentioning
confidence: 84%
“…Laboratory experiments on AB solutions have been performed in large water wave facility, installed at The University of Tokyo, that is 50 m long and 10 m wide while the water depth is 5 m (see Mozumi et al 2015;Waseda et al 2015 for a photography and a schematic description). The 11 wave gauges g i ∈ [g 1 , .…”
Section: Numerical Simulations and Experimental Set-upmentioning
confidence: 99%
“…NLS has since then been widely used in studies of modulation of water waves. In the case of two wave groups, the evolution of the envelope can be described by two coupled nonlinear Schrödinger equations (CNLS) [9][10][11][12][13]. CNLS has been used in stability problems in wave group evolution and it has been proved that under certain conditions the interaction of two wave groups can generate waves with very large wave height [10].…”
Section: Introductionmentioning
confidence: 99%